Screening and identification of fungi isolated from batik wastewaters for decolorization of Remazol Black B dye and batik effluent - Yasinta Swastika Ayu; Rina Sri Kasiamdari (Brawijaya University, 2022)
Azo dyes are the most commonly used dyes in the textile industry and is classified as reactive dyes, including remazol dyes. Remazol dye creates additional reactions with fibrous substrates to produce ester bonds that give the fabric a bright colour. Remazol Black B (RBB) is a reactive dye from the Azo group. Remazol, also called a reactive vinyl sulfone dye which is widely used in the batik industry with black B, is its kind of colour. One of the biological treatments uses bioremediation techniques using fungi as a bioremediation agent. Therefore, this study aimed to screen and identify potential fungi that could degrade RBB using tannic acid as a qualitative screening and quantitative screening using a liquid medium containing various concentrations of RBB dye (250 ppm, 500 ppm, 1000 ppm, 1500 ppm). The results showed among ninety-eight fungal isolates, and six isolates were positive for laccase assay using tannic acid. Two of the six fungal isolates were identified as Aspergillus sp.1 (74BRT) and Aspergillus sp.2 (105PDL), which were selected for further study based on their high efficiency in decolourising RBB dye (96.89% and 91.21%). BLAST analysis of sequence data showed the identity of isolate 74BRT as Aspergillus tamarii, and isolate 105PDL as Aspergillus sclerotiorum. The efficiency of A. tamarii and A. sclerotiorum to decolourise the batik effluent was up to 37.47% and 42.09%, respectively. The laccase assay of these two isolates showed that A. tamarii had the highest enzyme activity at 120 h, reaching 12.23 IU mL-1, while A. sclerotiorum reached 9.34 IU mL-1.